Heparanase expression and activity are increased in platelets during clinical sepsis. (11th March 2021) - Eustes, Alicia S.; Campbell, Robert A.; Middleton, Elizabeth A.; Tolley, Neal D.; Manne, Bhanu K.; Montenont, Emilie; Rowley, Jesse W.; Krauel, Krystin; Blair, Antoinette; Guo, Li; Kosaka, Yasuhiro; Medeiros‐de‐Moraes, Isabel M.; et al.
Abstract: Background: Heparanase (HPSE) is the only known mammalian enzyme that can degrade heparan sulfate. Heparan sulfate proteoglycans are essential components of the glycocalyx, and maintain physiological barriers between the blood and endothelial cells. HPSE increases during sepsis, which contributes to injurious glyocalyx degradation, loss of endothelial barrier function, and mortality. Objectives: As platelets are one of the most abundant cellular sources of HPSE, we sought to determine whether HPSE expression and activity increases in human platelets during clinical sepsis. We also examined associations between platelet HPSE expression and clinical outcomes. Patients/Methods: Expression and activity of HPSE was determined in platelets isolated from septic patients ( n  = 59) and, for comparison, sex‐matched healthy donors ( n  = 46) using complementary transcriptomic, proteomic, and functional enzymatic assays. Septic patients were followed for the primary outcome of mortality, and clinical data were captured prospectively for septic patients. Results: The mRNA expression of HPSE was significantly increased in platelets isolated from septic patients. Ribosomal footprint profiling, followed by [S35] methionine labeling assays, demonstrated that HPSE mRNA translation and HPSE protein synthesis were significantly upregulated in platelets during sepsis. While both the pro‐ and active forms of HPSE protein increased in platelets during sepsis, only the active form of HPSE protein significantly correlated with sepsis‐associated mortality. Consistent with transcriptomic and proteomic upregulation, HPSE enzymatic activity was also increased in platelets during sepsis. Conclusions: During clinical sepsis HPSE, translation, and enzymatic activity are increased in platelets. Increased expression of the active form of HPSE protein is associated with sepsis‐associated mortality.